2017
DOI: 10.1007/s11745-017-4297-3
|View full text |Cite
|
Sign up to set email alerts
|

Total Long‐Chain n‐3 Fatty Acid Intake and Food Sources in the United States Compared to Recommended Intakes: NHANES 2003–2008

Abstract: The American Heart Association recommends consuming fish (particularly oily fish) at least two times per week, which would provide ≈ 0.5 g/day of eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA) for cardiovascular disease risk reduction. Previous analyses indicate that this recommendation is not being met; however, few studies have assessed different ethnicities, subpopulations requiring additional n-3 fatty acid intake (i.e., children and pregnant and/or lactating women), or deciles of intake. Data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 32 publications
6
46
0
1
Order By: Relevance
“…Similar to previous findings for EPA and DHA in this population (Thompson et al, ), DPA intake was lower in women and younger age groups (<19 years), even when adjusting for differences in caloric needs between age groups. This pattern of DPA intake was also found in Norway (Johansson et al, ) and similar trends have been reported for EPA and DHA (Papanikolaou et al, ; Richter et al, ; Thompson et al, ). These differences may have implications for dietary recommendations and should be further explored.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar to previous findings for EPA and DHA in this population (Thompson et al, ), DPA intake was lower in women and younger age groups (<19 years), even when adjusting for differences in caloric needs between age groups. This pattern of DPA intake was also found in Norway (Johansson et al, ) and similar trends have been reported for EPA and DHA (Papanikolaou et al, ; Richter et al, ; Thompson et al, ). These differences may have implications for dietary recommendations and should be further explored.…”
Section: Discussionsupporting
confidence: 85%
“…Based on these potential health benefits, it is important to assess the usual DPA intake of the US population compared to habitual EPA and DHA intakes. The majority of the population in the United States (US) consume far less than the recommended amount of EPA and DHA (Papanikolaou et al, 2014;Richter et al, 2017; U.S. Department of Agriculture, Agricultural Research Service, 2014a; Zhang et al, 2018). For instance, an analysis of National Health and Nutrition Examination Survey (NHANES) data (2003)(2004)(2005)(2006)(2007)(2008) found that in US adults the mean intake of EPA and DHA from foods was 20 and 60 mg/day, and 40 and 70 mg/day when accounting for foods plus supplements (Papanikolaou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Richter et al reproduced with permission for direct comparison with the two oil replacement scenarios (Richter et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, median intakes were the lowest among Mexican Americans (0.09 g/day) and groups with higher EPA and DHA requirements (e.g. children [0.06–0.09 g/day] and women who were pregnant/lactating or of childbearing age [0.09–0.11 g/day]) (Richter et al, ).…”
Section: Introductionmentioning
confidence: 99%